ANALYSIS AND EVALUATION OF MOBILE APPLICATIONS FOR MANAGING DIABETES IN IRAQ FOR IMPROVING HEALTHCARE - Iman kadhim ajlan; Hayder Murad (Journal Park Publishing, 2023)
This research study aims to analyze and evaluate mobile applications for managing diabetes in Iraq. With the increasing prevalence of diabetes and the widespread use of mobiles, these applications have the potential to play a significant role in supporting diabetes management and improving healthcare outcomes. The research adopts a case study approach, focusing on a selected sample of mobile applications used by individuals with diabetes in Iraq. The evaluation criteria include the user interface, functionality, accuracy of information, accessibility, and user satisfaction. The findings of the study will provide insights into the strengths and weaknesses of existing applications and offer recommendations for enhancing their effectiveness in supporting diabetes management. The study also aims to contribute to the broader understanding of the potential of mobile applications in improving healthcare delivery for chronic diseases like diabetes.
Keywords: Mobile applications, diabetes management, Iraq, case study, evaluation, healthcare, user interface, functionality, information accuracy, accessibility, user satisfaction, chronic diseases.